AB0274 The Influence of Continuous Remission Rate on Functional Disability and Radiographic Progression for Rheumatoid Arthritis in A Japanese Observational Cohort. (10th June 2014) - Furu, M.; Hashimoto, M.; Ito, H.; Fujii, T.; Ishikawa, M.; Yamakawa, N.; Terao, C.; Yoshitomi, H.; Ogino, H.; Matsuda, S.; Mimori, T.
Abstract : Background: One goal of clinical remission in rheumatoid arthritis (RA) is to halt joint damage. The continuous clinical remission in established RA may result in improved function and reduced radiographic progression. Objectives: The authors assessed disease activity, functional disability and the progression of radiographic joint damage among RA patients in our Japanese observational cohort, and evaluated the relationship between continuous clinical remission and both functional disability and radiographic progression. Methods: We chose the 200 of consecutive RA patients, both with more than 6 months and with more than three visits during follow-up, and assessed clinical variables. The continuous remission rate over the entire period was defined, and assessed in comparison with the rate of functional remission and rapid radiographic progression (RRP). Results: The continuous remission rate was 38.9%, 23.7% and 25.7% for DAS28, CDAI and SDAI, respectively (table). The functional remission was achieved in 66.2%, 80.9% and 77.1% patients who fulfilled over 50% as continuous remission rate for DAS28, CDAI and SDAI, respectively (figure). RRP was observed in 27.6%, 25.0% and 30.0% patients who fulfilled less than 50%, and in 7.7%, 2.6% and 0% patients more than 50% as continuous remission rate for DAS28, CDAI and SDAI, respectively. Conclusions: SDAI and CDAI remission were more stringent for functional and radiographic assessment than DAS28 remission. The continuous clinical remission was associated with improved function and reduced radiographic progression in RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2782